2001
DOI: 10.34024/rnc.2011.v19.8323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Number of Animals per Cage on the Anxiety Levels in Mice

Abstract: original RESUMO Este estudo teve como objetivo avaliar o efeito do número de animais por gaiola sobre o comportamento de ansiedade em camundongos expostos ao labirinto em cruz elevado. Trinta camundongos foram divididos em dois grupos: grupo 1 (G1) e 2 (G2) com 10 e 20 animais, respectivamente, em cada gaiola. Ao atingir 90 dias de idade, cada animal foi submetido ao labirinto em cruz elevado, apenas uma vez no período de 5 minutos. Os parâmetros avaliados em ambos os grupos foram: porcentagem do número de ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Considering the higher anxiety levels observed in mice from the restricted cage ( Figure 2C ), it is also possible that poor reproductive performance is, at least partially, caused by unwell emotional states such as anxiety. Although breeding density varies proportionally with cage size for a certain group size, previous reports (Loo et al, 2001 ; Bellei et al, 2011 ; Buijs et al, 2011 ) did not find significant differences in reproductive performance between two groups of mice with different breeding densities (10 and 20 mice per cage, respectively) in the same cage with the size of (34 × 49 × 16 cm 3 ). The anxiety levels also showed no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Considering the higher anxiety levels observed in mice from the restricted cage ( Figure 2C ), it is also possible that poor reproductive performance is, at least partially, caused by unwell emotional states such as anxiety. Although breeding density varies proportionally with cage size for a certain group size, previous reports (Loo et al, 2001 ; Bellei et al, 2011 ; Buijs et al, 2011 ) did not find significant differences in reproductive performance between two groups of mice with different breeding densities (10 and 20 mice per cage, respectively) in the same cage with the size of (34 × 49 × 16 cm 3 ). The anxiety levels also showed no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 86%
“…Nowadays, much attention is being paid to the welfare of laboratory animals (Reeb-Whitaker et al, 2001;Gonder and Laber, 2007), and the conditions of keeping laboratory animals have been the focus of several studies, as environmental factors such as cage size may interfere with the results of behavioral tests (Loo et al, 2001;Mcglone et al, 2001;Wolfer et al, 2004;Julia et al, 2008). For example, previous studies have shown significant effects of cage size on reproductive performance (Julia et al, 2008;Whitaker et al, 2009), aggressiveness level (Loo et al, 2001), anxiety level (Bellei et al, 2011), and exploration and cognitive abilities (Forsyth and Young, 2007;Julia et al, 2008;Line et al, 2010). Therefore, animal welfare, including cage size, is critical to the reliability of research using laboratory animals.…”
Section: Introductionmentioning
confidence: 99%